EFFECTIVE APPROACH, WORK-RELATED CONTENT AND OPPORTUNITY TO PURSUE HIGHER EDUCATION OF SCIENCE CORE SUBJECTS - Mohd Razimi Husin; Hishamuddin Ahmad; Muhammad Bazlan Mustafa; Ismail @ Ismail Yusuf Panessai; Ramlan, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper presents the most effective approach used by teachers for the core subjects of Science, work-related learning content, and its future functions for humanities students in Sijil Pelajaran Malaysia. Previous research indicates there is a teenager that does not have a career to choose although they have a high academic performance. Moreover, there are teenagers who chose a career which have less relevance to the stream chosen at school. In this study, certain effective techniques and the very related contents of science core subject to future works has developed. This study uses a qualitative approach which involves interviews that are analysed using Nvivo software. The qualitative approach uses phenomenological design to reflect on the experience of the former students towards their experience and learning contents of secondary school upper-level science core subject which impacted their career aspirations today. Twelve experienced workers were selected through purposeful sampling. The results show that there are certain techniques that are very effective for teachers including the use of certain learning aids and science laboratories. Meanwhile, respondents who obtained very good examination results were less able to take advantage of Science Subjects in Sijil Pelajaran Malaysia (MCE) because most higher learning institutions tend to choose students who have biology or more relevant subjects in certain courses. This study has revealed effective learning experience techniques that are beneficial for all educators and also shows the lack of function of this science subject to students with excellent achievement.